2006
DOI: 10.1111/j.1440-1746.2006.04420.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased lipid peroxidation in patients with non‐alcoholic fatty liver disease and chronic hepatitis C as measured by the plasma level of 8‐isoprostane

Abstract: 8-Isoprostane values are elevated in patients with NAFLD and CH-C as compared to healthy controls. Oxidative stress caused by increased lipid peroxidation is involved in the pathogenesis of NAFLD and CH-C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 35 publications
5
54
1
Order By: Relevance
“…Patients infected with HCV show increases in lipid peroxidation levels in liver samples, serum, and peripheral blood mononuclear cells [72,[75][76][77][78][79][80]. In addition, other indicators of oxidative stress such as 4-hydroxynonenal and 8-hydroxydeoxyguanosine were found to be increased in HCV [72,74,[80][81][82][83].…”
Section: Viral Hepatitis and Free Radicalsmentioning
confidence: 99%
“…Patients infected with HCV show increases in lipid peroxidation levels in liver samples, serum, and peripheral blood mononuclear cells [72,[75][76][77][78][79][80]. In addition, other indicators of oxidative stress such as 4-hydroxynonenal and 8-hydroxydeoxyguanosine were found to be increased in HCV [72,74,[80][81][82][83].…”
Section: Viral Hepatitis and Free Radicalsmentioning
confidence: 99%
“…Changes in the lipid body compositions have been reported for patients with insulin-resistant NAFLD and have been characterized by 1) reduction in long-chain fatty acids, 2) increased n-6/n-3 PUFA ratios in liver and adipose tissue, 3) increased 18:1 n-9 trans levels in adipose tissue, 4) and elevated markers of hepatic lipid peroxidation and protein oxidation Konishi et al, 2006).…”
Section: Polyunsaturated Fatty Acids In Nonalcoholic Hepatic Steatosimentioning
confidence: 99%
“…While it might be expected that enhanced lipid peroxidation in NAFLD would be dependent, at least partially, on some lipidamic measures, there was little published support for such a correlation to date. Konishi et al [30] found no significant associations of plasma iPF 2α -Ⅲ with TC and TG in patients with NAFLD. In addition, Madan et al [31] failed to find relationship between oxidant stress and ALT levels in either NAFLD patients or diseased controls.…”
mentioning
confidence: 99%